Passenger behavioural intention to use selfservice check-in (SSCI) kiosks at KL International Airport (KLIA) / Mohd Fauzi Abdul Hamid - Abdul Hamid, Mohd Fauzi (Institute of Graduate Studies, UiTM, 2018)
The self-service check-in (SSCI) KLIA kiosk is a platform that is governed by an airline's application interface for passenger check-in and the printing of boarding passes. Today's travelling passengers have the strong desire that they be a co-producer of the check-in process and they want to do it quickly. Passengers' behavioural intentions vary towards the use of the SSCI KLIA kiosks. Thus, a complete understanding of the factors influencing passengers' behavioural intentions when using SSCI KLIA kiosks in different contexts was deemed necessary. This study focused on examining the external factors that were thought to directly affect behavioural intention to use SSCI KLIA kiosks, namely, perceived control, perceived convenience and perceived speed. The Technology Acceptance Model (TAM) has been the theory that is most widely used to explain an individual's acceptance of information technology (IT) and information systems (IS). This quantitative study has extended the TAM in the context of SSCI KLIA kiosks. This research focuses on the model development and it empirically validates the conceptual framework of a SSCI KLIA kiosk Behavioural Intention Model using the structural equation model (SEM). Hence, the differences in this study were evaluated to understand the modifications that were made to this model. A non-probability sampling design and specifically purposive sampling, was applied in this study. Empirical data from 320 valid respondents was collected through a personally assisted survey using a 37-item structured questionnaire…